2023
DOI: 10.1111/cup.14404
|View full text |Cite
|
Sign up to set email alerts
|

Novel ANKRD26 and PDGFRB gene mutations in pediatric case of non‐Langerhans cell histiocytosis: Case report and literature review

Abstract: Cutaneous non‐Langerhans cell histiocytosis (NLCH) is a rare and biologically benign entity that can be broadly classified into two categories: xanthogranuloma and non‐xanthogranuloma. The xanthogranuloma family is characterized by a proliferation of histiocytes with both macrophage and dendritic cell differentiation, negative BRAF mutation, and rare Touton‐type giant cells. Molecular studies have reported that mutations involved in the MAPK signaling pathways are implicated in the pathophysiology of histiocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This fusion lacked an open reading frame to drive the translation of a functional fusion protein [56]. Additionally, a 2023 published case study identified a PDGFRB::CD74 fusion mRNA in a 19-month-old female patient diagnosed with an aggressive case of cutaneous non-Langerhans cell histiocytosis (NLCH) [146]. Although the biopsy specimen was benign, the mutations that led to the PDGFRB::CD74 fusion mRNA had not been previously associated with pediatric or adult NLCH [146].…”
Section: Cd74-pdgfrb Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fusion lacked an open reading frame to drive the translation of a functional fusion protein [56]. Additionally, a 2023 published case study identified a PDGFRB::CD74 fusion mRNA in a 19-month-old female patient diagnosed with an aggressive case of cutaneous non-Langerhans cell histiocytosis (NLCH) [146]. Although the biopsy specimen was benign, the mutations that led to the PDGFRB::CD74 fusion mRNA had not been previously associated with pediatric or adult NLCH [146].…”
Section: Cd74-pdgfrb Expressionmentioning
confidence: 99%
“…While this fusion has been documented in the literature several times, its oncogenic variant remains to be further studied and characterized as the oncogenic signaling pathway that is activated is still unknown. But, it is likely that the presence of CD74-PDGFRB leads to the activation of PDGFRB [146].…”
Section: Cd74-pdgfrb Expressionmentioning
confidence: 99%